Perancangan Aplikasi E-Commerce FDW Store menggunakan Metode Lean UX - Felik Darmawan Wijaya; Magdalena Ariance Ineke Pakereng (KITA Institute, 2023)
FDW Store is an online store that sells services to meet the needs of users' games and lives. FDW Store sells services such as credit for all operators, Online Game Top Up, Payment Point Online Bank (PPOB). The problem that occurs in FDW Store business owners is that they do not have a proper FDW Store application display design and have been tested if they want to be built into an application that is ready to use. Based on these problems, the solution is to design the UI/UX of the mobile-based FDW Store E-Commerce Application using the Lean UX method because this method has the advantage of a fast success rate and also focuses on understanding the experience of the product to be made. This study resulted in the design of the User Interface (UI) and User Experience (UX) for the FDW Store E-Commerce application which is useful as a reference for business owners in building an application.